Efficiency of superficial and incorporated liming on a hapludalf prior to no-tillage implementation Eficiência da calagem superficial e incorporada precedendo o sistema plantio direto em um argissolo sob pastagem natural - Kaminski J. (2005)
Liming alters chemical soil attributes and favors root development, but its efficiency depends on the incorporation form and the physical and chemical characteristics of the soil. This experiment was carried out to evaluate the efficiency of incorporated or surface liming seven years after its application on a Hapludalf under no-tillage system and located in Santa Maria, RS, Brazil. The replicated treatments.consisted of four surface lime rates (0.0; 2.0, 8.5 and 17.0 t ha-1), incorporated by one plowing followed by two diskings. Independent of the initial incorporation, the 2.01 ha-1 rate was reapplied over the surface every 24 months. After seven years of cultivation, three trenches were dug in each plot to collect soil samples every 1 cm in the 0-10 cm layer, every 2.5 cm in the 10-25 cm layer and every 5 cm in the 25-40 cm layer. Results showed that liming effects are still detectable after seven years of its application, regardless of the application form. Recommended lime rates applied at once promoted the advance of an acidity neutralization front furthest down into the soil. Incorporating lime before no-tillage implementation neutralized acidity to deeper soil layers and was more effective than surface application.